Basic Mathematical Literacy Skills Ability by Van Hiele Project Based Learning Theory - Sumarto, Hadi; Junaedi, Iwan; Ahmadi, Farid; Marwoto, Putut; Sumarni, Woro (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
Mathematical literacy is a person's ability to formulate, apply, and interpret mathematics. The fact that Mathematical Literacy Skills is the main challenge in learning basic mathematics and can also be used as a key to explore mathematics learning. This article aims to analyze basic mathematical skills related to Van Hiele's project-based learning theory. The following type of research is qualitative research. The subjects of this research are fourth grade students at SDN 2 Korowelanganyar Cepiring Kendal. The instruments used in the study were tests and interviews. The results of the following research show that SDN 2 Korowelanganyar improves students' geometric reasoning abilities and the characteristics of fourth grade geometric reasoning by learning basic mathematical knowledge related to Van Hiele's theory. This shows that learning basic mathematical knowledge by van Hiele's project-based learning theory can improve students' ability to solve geometry problems.Literasi matematik ialah kemampuan seseorang untuk merumuskan, menerapkan, serta menafsirkan matematika. Fakta bahwa literasi matematika adalah tantangan utama dalam pembelajaran matematika dasar serta juga bisa digunakan sebagai kunci untuk mengeksplorasi pembelajaran matematika. Artikel ini bertujuan untuk menganalisis keterampilan matematika dasar yang terkait dengan teori pembelajaran berbasis proyek Van Hiele. Jenis riset berikut ialah penelitian kualitatif. Subyek riset berikut ialah peserta didik kelas IV SDN 2 Korowelanganyar Cepiring Kendal. Instrumen yang digunakan dalam penelitian ialah tes serta wawancara. Hasil riset berikut menunjukkan bahwa SDN 2 Korowelanganyar meningkatkan kemampuan penalaran geometrik peserta didik serta karakteristik penalaran geometrik kelas IV dengan mempelajari pengetahuan matematika dasar yang berkaitan dengan teori Van Hiele. Ini menunjukkan bahwa dengan mempelajari pengetahuan matematika dasar oleh teori pembelajaran berbasis proyek van Hiele mampu meningkatkan kememampuan peserta didik dalam menyelesaikan soal geometri.